Earnings and Dividend Announcements, Semi-Strong Efficiency and the Nigerian Stock Market: An Empirical Investigation - Ogege, Samson; Ogbulu, Onyemachi Maxwell; Isu, Hamilton Obianyi (Archives of Business Research, 2015)
The major objective of this paper is to find out whether stock prices adjust to dividend and earnings announcements in the Nigerian Stock Exchange. The study is anchored on the Efficient Market Hypothesis (EMH) and we adopted the Event Study methodology for the period of six years ranging from 2006-2011. The modified market model was also adopted to investigate whether the Nigerian Stock Market reacts efficiently to dividend and earnings announcements with respect to price adjustment. The findings of our study reveal that stock prices in the Nigerian stock market did adjust efficiently to dividend and earnings announcements in the three sub-periods covered by our sample. In addition, the cumulative average abnormal returns for the different combinations of dividend and earnings in the three sub-periods are not significant suggesting that the Nigerian stock market is semi-strong efficient. This shows that the Nigerian Stock market did react efficiently to publicly available information such as dividend and earnings announcements during the three sub-periods of pre-global financial crisis (2006-2007); the global financial crisis (2008-2009); and the post global financial crisis of (2010-2011). Based on these findings, the authors recommend that the Nigerian Stock market should vigorously sustain the numerous capital market reforms adopted over the years to further address the issue of adequate communication infrastructure, ease of accessibility of publicly available information, regular review of policies and regulation of the market as well as guide against the issue of insider dealing as this will enhance further efficiency of the Nigerian stock market. Keywords: Event Study, Semi-Strong Efficiency, Dividend and Earnings announcement, Cumulative abnormal returns.